Analisis Total Productive Maintenance Pada Needle Detector Divisi Packing - Nur Muchlisin; Dian Janari (Lembaga Penelitian dan Pengabdian pada Masyarakat, Universitas Buana Perjuangan Karawang, 2021)
PT. Mataram Tunggal Garment is a company that produces clothes with 100% of their production being exported to various countries. To maintain machine productivity, one of the factors to pay attention to is maintenance. This research focuses on needle detector conveyors in the packing division to determine the actual condition of the conveyors. Conveyor availability value in January is 100%. In February the availability value decreased to 97.1% due to the conveyor breakdown with a frequency of 1 time. 6 hours of repair time required. For March, the availability value is in 100% condition, which indicates the conveyor is in optimal condition. Suggestions for improvements that are proposed include improving technician skills to better understand the machine in question so that damage handling is faster. Recording every maintenance time is also very necessary to reduce the potential for damage to the machine considering that the longer the engine part is used, it will shrink. In addition to checking the part replacement process can be carried out if needed. Machine operators must understand the proper operation of the machine and perform maintenance independently